5.2k views
0 votes
What is the product of (3x-9) and 6x↑2-2x+5 Write your answer in standard form.

(a) Show your work.

(b) Is the product of (3x-9) and 6x↑2-2x+5 equal to the product of (9x-3) and 6x↑2-2x+5

Explain your answer.

User CoolMcGrrr
by
4.5k points

1 Answer

3 votes

Answer:

a.
18x^3 -60x^2 + 33x - 45

b. No

Explanation:

Given:

(3x-9) and
6x^2-2x+5

=> the production of them is:


(3x-9)(6x^2-2x+5) , we will use distributive law to solve this To do that. we first multiply
6x^2-2x+5 by 3x then by -9. This is done as follows

=
3x (6x^2-2x+5) - 9(6x^2-2x+5)
= (3x * 6x^2-3x * 2x+3x *5) - (9* 6x^2-9* 2x+9* 5)\\\\= (18x^3 -6x^2+ 15x) - (54x^2 - 18x +45)

Then Open both brackets

=
18x^3 -6x^2+ 15x -54x^2 + 18x -45

After that, we group the same terms

=
18x^3 -(6x^2 +54x^2)+ (15x + 18x) -45

=
18x^3 -60x^2 + 33x - 45

(b) Is the product of (3x-9) and
6x^2-2x+5 equal to the product of (9x-3) and
6x^2-2x+5

No, let find the product of (9x-3) and
6x^2-2x+5 , we will use distributive law to solve this as the above example.

= (9x-3)
(6x^2-2x+5)

=
9x (6x^2-2x+5) - 3(6x^2-2x+5)

=
(9x * 6x^2 - 9x * 2x + 9x *5) - (3* 6x^2 - 3 * 2x + 3* 5)

=
(54x^3 - 18x^2+ 45x) - (18x^2 - 6x +15)

After that, we open the bracket to find the same terms

=
54x^3 - 18x^2+ 45x -18x^2 + 6x -15

=
54x^3 - 18x^2 -18x^2 + 45x + 6x -15

=
54x^3 - 36x^2 + 51x -15

As you can see
54x^3 - 36x^2 + 51x -15
18x^3 -60x^2 + 33x - 45

Hope it will find you well.

User RaviRokkam
by
4.7k points